Topical Capsaicin Therapy for Uremic Pruritus in Patients on Hemodialysis (Iranian Journal of Kidney Diseases, 2010)
Introduction. Pruritus is one of the common problems in patients on hemodialysis. There are several causes for pruritus, and different treatment modalities are applied to control it. The aim of this study was to evaluate the therapeutic effect of capsaicin on pruritus, compared with placebo, in patients on hemodialysis.Materials and Methods. This randomized double-blinded cross-over clinical trial was performed on 34 patients on hemodialysis with uremic pruritus. The patients were divided into 2 groups, one group received capsaicin 0.03% and the other, placebo, for 4 weeks. Treatment was stopped for 2 weeks as washout period and continued as a cross-over technique. Pruritus scores were analyzed and compared.Results. Thirty-four patients on long-term hemodialysis, 14 men and 20 women with a mean age of 57.0 ± 18.6 years were studied. The mean of pruritus score before capsaicin treatment was 15.9 ± 6.3, which was reduced to 6.4 ± 3.9, 4.7 ± 3.1, 3.2 ± 2.9, and 2.5 ± 2.5 on weeks 1 to 4, respectively (P < .001). In the placebo group, pruritus score before treatment was 15.0 ± 6.0 on average, and it was 11.7 ± 5.8, 9.4 ± 5.9, 7.9 ± 5.5, and 7.2 ± 5.5, respectively, on weeks 1 to 4 (P < .001). There was no significant difference in pruritus scores before the treatment between the two groups, but after each week, the difference was significant (P < .001). Repeated measurement test showed that decreasing in pruritus severity in the capsaicin group was more than that in the placebo group during treatment period (P < .001).Conclusions. Capsaicin is a new safe and effective topical treatment for hemodialysis-induced pruritus in patients with end-stage renal disease.